Polyolefin composition having excellent impact strength and light transmittance
By using compositions of ethylene/α-olefin multiblock interpolymer and propylene homopolymer in automotive components, the problem of difficulty in maintaining characteristics over a wide temperature range is solved, and excellent mechanical and optical properties are achieved.
Patent Information
- Application Number
- CN202380066249.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-25
AI Technical Summary
Existing ethylene/α-olefin elastomers have difficulty maintaining excellent mechanical and optical properties over a wide temperature range, especially in the manufacture of translucent automotive parts.
A composition is employed that comprises at least one ethylene/α-olefin multiblock interpolymer and at least one propylene homopolymer, and the component a is present in an amount of ≤50% by weight based on the weight of components a and b.
Excellent mechanical properties (such as toughness and stiffness) and optical properties (such as light transmittance and light diffusion) are achieved over a wide temperature range of 0°C to 60°C.
Smart Images

Figure CN119894975A_ABST
Abstract
Description
Background Art
[0001] Ethylene / α-olefin elastomers have been used as impact modifiers for polypropylene for decades. Such TPO compounds are common in the automotive industry, where they are used to make interior and exterior automotive parts such as bumper skins, door trim panels, airbag covers, and many other parts. Currently, there is a new trend for translucent parts on electric vehicles, especially the ability of the front grille and / or rear bumper to transmit light. These translucent design features cannot be achieved with current TPO compositions. New compositions that provide excellent mechanical properties (e.g., toughness and stiffness) and excellent optical properties (e.g., percent transmittance) are needed. In addition, these features need to remain adequate over a wide temperature range (e.g., 0°C to 60°C).
[0002] U.S. Patent No. 8,921,491 discloses an impact modified composition comprising an ethylene-α-olefin (block) interpolymer characterized by an average block index ABI greater than zero and up to about 1.0 and a molecular weight distribution MWD greater than about 1.3. Additionally, or alternatively, the block ethylene / α-olefin interpolymer is characterized by having at least one fraction obtained by temperature rising elution fractionation (TREF), and wherein the fraction has a block index greater than about 0.3 and up to about 1.0, and the ethylene / α-olefin interpolymer has a molecular weight distribution MWD greater than about 1.4 (see Abstract). The "Soft Segment Tm (°C) from Weighted DSC" for several polymers is listed in Table 16 (see column 72, lines 6-29). For compositions containing propylene homopolymers, see, for example, Table 27 (column 81) and Table 32 (column 85).
[0003] U.S. Patent No. 7,893,166 discloses a class of ethylene / α-olefin block interpolymers characterized by an average block index ABI greater than zero and up to about 1.0 and a molecular weight distribution MWD greater than about 1.3. Preferably, the block index is from about 0.2 to about 1. Additionally, or alternatively, the block ethylene / α-olefin interpolymer is characterized by having at least one fraction obtained by temperature rising elution fractionation (TREF), wherein the fraction has a block index greater than about 0.3 and up to about 1.0, and the ethylene / α-olefin interpolymer has a molecular weight distribution MWD greater than about 1.3 (see Abstract). The "soft segment Tm (°C) from weighted DSC" for several polymers is listed in Table 16 (see column 60, lines 11-35). The patent discloses polymers for blending, including polypropylene (see, e.g., column 25, lines 11-33). See also U.S. Patent No. 7,608,668.
[0004] U.S. Patent No. 10,557,005 discloses a painted article including a primer layer between a substrate and a paint layer. The substrate is the product of a composition forming a substrate, the composition comprising an olefin block copolymer and a polypropylene polymer having a density of 0.89 g / cc to 0.92 g / cc (see Abstract). Such compositions containing a majority amount of the olefin block copolymer are shown in Tables 4 and 5.
[0005] Additional compositions and / or parts (such as automotive parts) are described in the following references: U.S. Patent 7947793, U.S. Patent 8084537, U.S. Patent 7592397, U.S. Patent 7863379, U.S. Patent 8573665, U.S. Patent 5925703, U.S. Patent 8455087, U.S. Patent 7741397, U.S. Publication 2015 / 0291085, U.S. Publication 2012 / 0313392, International Publication WO2014 / 036292 and GB2552996A.
[0006] However, as discussed above, there remains a need for new compositions that provide excellent mechanical properties and excellent optical properties that remain adequate over a wide temperature range. This need has been met by the following invention. Summary of the invention
[0007] A composition comprising a first composition, wherein the first composition comprises at least the following components a and b:
[0008] a) at least one ethylene / α-olefin multi-block interpolymer comprising a density ≥ 0.870 g / cc and
[0009] Soft segment melting temperature (SS-Tm) ≤35°C;
[0010] b) a polymer composition comprising at least one propylene homopolymer, and
[0011] The component a is present in an amount of ≤50% by weight based on the weight of components a and b. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 Plotted are the "Melting Enthalpy (J / g) versus Temperature (°C)" for the linear copolymers described herein. Figure 2 Three test samples (ductile, semi-brittle and brittle) from a multi-axial dart impact (dart ductility) test are depicted. Figure 3 A photograph depicting two TPO panels over an LED light source. DETAILED DESCRIPTION
[0013] Compositions having excellent mechanical properties (eg, toughness and stiffness) and excellent optical properties (eg, light transmittance and light diffusivity) have been found. In addition, these properties remain adequate over a wide temperature range (eg, 0°C to 60°C).
[0014] As discussed above, a composition is provided, and the composition comprises a first composition, the first composition comprising at least the following components a and b: a) at least one ethylene / α-olefin multi-block interpolymer comprising a density ≥0.870 g / cc and a soft segment melting temperature (SS-Tm) ≤35°C; b) a polymer composition comprising at least one propylene homopolymer, and wherein the component a is present in an amount ≤50 wt% based on the weight of components a and b.
[0015] The above composition may include a combination of two or more embodiments as described herein. The first composition may include a combination of two or more embodiments as described herein. Each component a and b may independently include a combination of two or more embodiments as described herein.
[0016] In one embodiment or a combination of two or more embodiments each described herein, the ethylene / α-olefin multi-block interpolymer (of component a) has a density of ≥ 0.870 g / cc, or ≥ 0.871 g / cc, or ≥ 0.872 g / cc, or ≥ 0.873 g / cc, or ≥ 0.874 g / cc, or ≥ 0.875 g / cc, or ≥ 0.876 g / cc, or ≥ 0.877 g / cc, or ≥ 0.878 g / cc, or ≥ 0.879 g / cc, or ≥ 0.880 g / cc, or ≥ 0.881 g / cc, or ≥ 0.882 g / cc, or ≥ 0.883 g / cc, or ≥ 0.884 g / cc. In one embodiment or a combination of two or more embodiments each described herein, the ethylene / α-olefin multi-block interpolymer (of component a) has a density of ≤0.910 g / cc, or ≤0.908 g / cc, or ≤0.906 g / cc, or ≤0.904 g / cc, or ≤0.902 g / cc, or ≤0.900 g / cc, or ≤0.898 g / cc, or ≤0.896 g / cc, or ≤0.894 g / cc, or ≤0.892 g / cc, or ≤0.890 g / cc, or ≤0.889 g / cc, or ≤0.888 g / cc, or ≤0.887 g / cc.
[0017] In one embodiment or a combination of two or more embodiments each described herein, the ethylene / α-olefin multi-block interpolymer (of component a) has a SS-Tm of ≤35°C, or ≤30°C, or ≤25°C, or ≤20°C, or ≤18°C, or ≤16°C, or ≤14°C, or ≤12°C, or ≤10°C, or ≤9°C, or ≤8°C, or ≤7°C, or ≤6°C. In one embodiment or a combination of two or more embodiments each described herein, the ethylene / α-olefin multi-block interpolymer (of component a) has a SS-Tm of ≥-20°C, or ≥-18°C, or ≥-16°C, or ≥-14°C, or ≥-12°C, or ≥-10°C, or ≥-8°C, ≥-6°C, or ≥-4°C, or ≥-2°C, or ≥-1°C, or ≥0°C, or ≥1°C, or ≥2°C, or ≥3°C, or ≥4°C.
[0018] In one embodiment or a combination of two or more embodiments each described herein, the ethylene / α-olefin multi-block interpolymer (of component a) is an ethylene / α-olefin multi-block copolymer.
[0019] In one embodiment or a combination of two or more embodiments each described herein, the ethylene / α-olefin multi-block interpolymer (of component a) has ≥ 0.1 g / 10 min, or ≥ 0.2 g / 10 min, or ≥ 0.3 g / 10 min, or ≥ 0.4 g / 10 min, or ≥ 0.5 g / 10 min and / or ≤ 50 g / 10 min, or ≤ 45 g / 10 min, or ≤ 40 g / 10 min, or ≤ 35 g / 10 min, or ≤ 30 g / 10 min, or ≤ 28 g / 10 min. in, or ≤26 g / 10 min, or ≤24 g / 10 min, or ≤22 g / 10 min, or ≤20 g / 10 min, or ≤18 g / 10 min, or ≤16 g / 10 min, or ≤14 g / 10 min, or ≤12 g / 10 min, or ≤10 g / 10 min, or ≤9.0 g / 10 min, or ≤8.0 g / 10 min, or ≤7.0 g / 10 min, or ≤6.0 g / 10 min, or ≤5.0 g / 10 min melt index (MI or I2).
[0020] In one embodiment or a combination of two or more embodiments each as described herein, the propylene homopolymer (of component b) has a melt flow rate (MFR) of ≥ 1.0 g / 10 min, or ≥ 2.0 g / 10 min, or ≥ 3.0 g / 10 min, or ≥ 4.0 g / 10 min, or ≥ 5.0 g / 10 min, or ≥ 10 g / 10 min, or ≥ 20 g / 10 min, or ≥ 25 g / 10 min and / or ≤ 200 g / 10 min, or ≤ 150 g / 10 min, or ≤ 100 g / 10 min, or ≤ 90 g / 10 min, or ≤ 80 g / 10 min, or ≤ 75 g / 10 min, or ≤ 70 g / 10 min, or ≤ 68 g / 10 min, or ≤ 66 g / 10 min.
[0021] In one embodiment or a combination of two or more embodiments each as described herein, component b comprises at least two propylene homopolymers (first and second), and wherein the melt flow rate (MFR hPP1 ) is greater than the melt flow rate (MFR) of the second homopolymer hPP2 ).
[0022] In one embodiment or a combination of two or more embodiments each as described herein, wherein the melt flow rate (MFR hPP1 ) is ≥10g / 10min, or ≥20g / 10min, or ≥40g / 10min, or ≥60g / 10min, or ≥80g / 10min, or ≥100g / 10min and / or ≤1000g / 10min, or ≤800g / 10min, or ≤600g / 10min, or ≤400g / 10min, or ≤300g / 10min, or ≤200g / 10min, or ≤150g / 10min, or ≤120g / 10min.
[0023] In one embodiment or a combination of two or more embodiments each as described herein, wherein the MFR hPP1 / MFR hPP2 The ratio is >1.0, or ≥2.0, or ≥5.0, or ≥7.0, or ≥10 and / or ≤50, or ≤45, or ≤40, or ≤35, or ≤30.
[0024] In one embodiment or a combination of two or more embodiments each as described herein, the weight ratio of the first homopolymer to the second homopolymer is ≥0.10, or ≥0.20, or ≥0.40, or ≥0.50, or ≥0.60, or ≥0.80, or ≥1.0, or ≥1.2, or ≥1.4, or ≥1.5 and / or ≤10, or ≤8.0, or ≤6.0, or ≤4.0, or ≤2.0, or ≤1.8, or ≤1.6.
[0025] In one embodiment or a combination of two or more embodiments each as described herein, the weight ratio of component b to component a is ≥1.0, or ≥1.2, or ≥1.4, or ≥1.6, or ≥1.8 and / or ≤10, or ≤9.0, or ≤8.0, ≤7.0, or ≤6.0, or ≤5.5, or ≤5.0, or ≤4.5, or ≤4.0, or ≤3.5, or ≤3.0.
[0026] In one embodiment or a combination of two or more embodiments each as described herein, the first composition comprises ≥80 wt.-%, or ≥85 wt.-%, or ≥90 wt.-%, or ≥92 wt.-%, or ≥94 wt.-%, or ≥96 wt.-%, or ≥98 wt.-% of components a and b, based on the weight of the first composition. In one embodiment or a combination of two or more embodiments each as described herein, the first composition comprises ≤100 wt.-% or ≤99 wt.-% of components a and b, based on the weight of the first composition.
[0027] In one embodiment or a combination of two or more embodiments each described herein, the first composition comprises at least two crystallization peaks (a first peak and a second peak), and wherein the second peak and the first peak are the peaks having the highest and second highest crystallization temperatures, respectively, and wherein the second peak and the first peak each independently have a crystallization temperature of ≥100°C.
[0028] In one embodiment or a combination of two or more embodiments each described herein, the first crystallization peak has a crystallization temperature of ≥100°C, or ≥102°C, or ≥104°C, or ≥106°C, or ≥108°C, or ≥110°C, or ≥116°C, or ≥112°C, or ≥114°C, or ≥116°C and / or ≤140°C, or ≤138°C, or ≤138°C, ≤134°C, or ≤132°C, or ≤130°C, or ≤128°C, or ≤126°C, or ≤124°C.
[0029] In one embodiment or a combination of two or more embodiments each described herein, the second crystallization peak has a crystallization temperature that is ≥5°C, or ≥7°C, or ≥10°C, or ≥12°C, or ≥14°C, or ≥16°C, or ≥18°C, or ≥20°C, or ≥22°C, or ≥25°C, or ≥27°C, or ≥30°C, or ≥32°C, or ≥35°C, or ≥37°C, or ≥40°C, or ≥42°C, or ≥45°C, or ≥47°C, or ≥50°C higher than the crystallization temperature of the first crystallization peak.
[0030] In one embodiment or a combination of two or more embodiments each described herein, the intensity (in Watts / g) of each of the first crystallization peak and the second crystallization peak independently satisfies the following relationship: [(peak intensity) - (average baseline intensity)] ≤ -0.05 Watts / g, further ≤ -0.10 Watts / g, further ≤ -0.15 Watts / g, further ≤ -0.20 Watts / g, further ≤ -0.25 Watts / g, further ≤ -0.30 Watts / g, further ≤ -0.35 Watts / g. "Average baseline intensity (in Watts / g)" = [(heat flow at 160°C (Watts / g)) - (heat flow at -40°C (Watts / g))] / 2.
[0031] In one embodiment or a combination of two or more embodiments each as described herein, the composition has an MFR ≥ 5.0 g / 10 min, or ≥ 7.0 g / 10 min, or ≥ 10 g / 10 min, or ≥ 12 g / 10 min, or ≥ 15 g / 10 min, or ≥ 18 g / 10 min, or ≥ 20 g / 10 min and / or ≤ 50 g / 10 min, or ≤ 45 g / 10 min, or ≤ 40 g / 10 min, or ≤ 35 g / 10 min, or ≤ 30 g / 10 min, or ≤ 25 g / 10 min.
[0032] In one embodiment or a combination of two or more embodiments each as described herein, the composition has a light transmittance (3.2 mm thickness) at room temperature (23°C) ≥30%, or ≥35%, or ≥40%, or ≥45%, or ≥50%, or ≥55%, or ≥60% and / or ≤100%, or ≤95%.
[0033] In one embodiment or a combination of two or more embodiments each as described herein, the composition has a % change in transmittance that satisfies the following relationship: [(transmittance (3.2 mm thickness) at room temperature (23°C)) - (transmittance (3.2 mm thickness) at 60°C)] ≤ 15%, or ≤ 14%, or ≤ 13%, or ≤ 12%, or ≤ 11%, or ≤ 10%, or ≤ 9.0%, or ≤ 8.0%, or ≤ 7.0%, or ≤ 6.0%, or ≤ 5.0%.
[0034] In one embodiment or a combination of two or more embodiments each as described herein, the composition has a dart ductility at -10°C (2.2 m / s) ≥ 90%, or ≥ 95%, or ≥ 100%. In one embodiment or a combination of two or more embodiments each as described herein, the composition has a dart ductility at -30°C (2.2 m / s) ≥ 90%, or ≥ 95%, or ≥ 100%.
[0035] In one embodiment or a combination of two or more embodiments each as described herein, the composition has an Izod notch at -30°C of ≥ 3 kJ / m 2 , or ≥4kJ / m 2 , or ≥5kJ / m 2 , or ≥6kJ / m 2 , or ≥7 kJ / m 2 , or ≥8kJ / m 2 , or ≥9kJ / m 2 , or ≥10kJ / m 2 In one embodiment or a combination of two or more embodiments each as described herein, the composition has an Izod notch at 23°C of ≥ 10 kJ / m 2 , or ≥15kJ / m 2 , or ≥20kJ / m 2 , or ≥25kJ / m 2 , or ≥30kJ / m 2 , or ≥35kJ / m 2 , or ≥40kJ / m 2 , or ≥45kJ / m 2 , or ≥50kJ / m 2 .
[0036] In one embodiment or a combination of two or more embodiments each as described herein, the composition has a flexural modulus of ≥ 800 MPa, or ≥ 900 MPa, or ≥ 1000 MPa.
[0037] In one embodiment or a combination of two or more embodiments each as described herein, the composition has the following properties a) to g): a) MFR ≥ 10 g / min, b) light transmittance (3.2 mm thickness) ≥ 30% at room temperature (23°C), c) dart drop ductility (2.2 m / s) ≥ 90% at -10°C, d) Izod notch at -30°C ≥ 4 kJ / m 2 , e) cantilever beam notch at 23℃≥35kJ / m 2, f) flexural modulus ≥ 800 MPa, and g) [(light transmittance (3.2 mm thickness) at room temperature (23°C)) - (light transmittance (3.2 mm thickness) at 60°C))] ≤ 10%.
[0038] The present invention also provides an article comprising at least one component formed from a composition of one embodiment or a combination of two or more embodiments each as described herein. In another embodiment, the article is an automotive component.
[0039] Also provided is a method of forming an automotive part comprising mixing the composition of one embodiment or a combination of two or more embodiments each as described herein.
[0040] Ethylene / α-olefin multi-block interpolymer
[0041] Ethylene / α-olefin multi-block interpolymers and copolymers comprise ethylene and α-olefins in polymerized form. α-olefins include, but are not limited to, C3-C20 α-olefins, further C3-C10 α-olefins, further C3-C8 α-olefins, such as propylene, 1-butene, 1-pentene, 1-hexene and 1-octene.
[0042] Ethylene / α-olefin multi-block interpolymers are characterized by multiple blocks or segments of two or more polymerized monomer units, with different chemical or physical properties. In some embodiments, multi-block interpolymers, and further copolymers, can be represented by the following formula: (AB) n, wherein n is at least 1, preferably an integer greater than 1, such as 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100 or more. In this article, "A" represents a hard block or segment, and "B" represents a soft block or segment. Preferably, the A segment and the B segment are connected (or covalently bonded) in a substantially straight chain manner opposite to a substantially branched or substantially star-shaped manner. In other embodiments, the A segment and the B segment are randomly distributed along the polymer chain. In other words, for example, the block interpolymer does not generally have the following structure: AAA-AA-BBB-BB. In other embodiments, the block interpolymers generally do not have a third type of block or segment, which includes one or more different comonomers. In yet other embodiments, block A and block B each have monomers or comonomers that are substantially randomly distributed within the block. In other words, block A and block B do not contain two or more sub-segments (or sub-blocks) of different compositions, such as end segments, which have compositions that are substantially different from the rest of the block.
[0043] As used herein, the term "hard segment (HS)" refers to a block of polymerized monomer units, wherein ethylene is present in an amount of, for example, >90 mol%, or ≥92 mol%, or ≥95 mol%, or ≥98 mol%, or ≥99 mol%, based on the total moles of polymerized monomers in the block. In one embodiment, ethylene is present in an amount of ≤99.8 mol%, or ≤99.6 mol%, or ≤99.4 mol%, or ≤99.3 mol%, based on the total moles of polymerized monomers in the block.
[0044] As used herein, the term "soft segment (SS)" refers to a block of polymerized monomer units, wherein ethylene is present in an amount of, for example, ≤90 mol%, or ≤88 mol%, or ≤86 mol%, or ≤84 mol%, or ≤82 mol%, based on the total moles of polymerized monomers in the block. In one embodiment, ethylene is present in an amount of ≥60 mol%, or ≥65 mol%, or ≥70 mol%, or ≥75 mol%, or ≥80 mol%, based on the total moles of polymerized monomers in the block.
[0045] The soft segment can be present in the ethylene / octene multi-block interpolymer in an amount of 1 wt %, or 5 wt %, or 10 wt %, or 15 wt %, or 20 wt %, or 25 wt %, or 30 wt %, or 35 wt %, or 40 wt %, or 45 wt % to 50 wt %, or 55 wt %, or 60 wt %, or 65 wt %, or 70 wt %, or 75 wt %, or 80 wt %, or 85 wt %, or 90 wt %, or 95 wt %, or 99 wt % of the total weight of the ethylene / octene multi-block interpolymer. In contrast, the hard segment can be present in a similar range. The soft segment weight percentage and the hard segment weight percentage can be calculated based on the data obtained from DSC or NMR. Such methods and calculations are disclosed in, for example, USP 7,608,668, the disclosure of which is incorporated herein by reference in its entirety. For example, the weight percentages of hard and soft segments can be determined as described in columns 57 to 63 of US Patent 7,608,668, which is incorporated herein by reference.
[0046] Typically, ethylene accounts for 50 mole percent or a majority of the mole percent of the entire multi-block interpolymer; that is, ethylene accounts for at least 50 mole percent of the entire interpolymer. More preferably, ethylene accounts for at least 60 mole percent, or at least 70 mole percent, or at least 80 mole percent, or at least 90 mole percent, while the remaining portion of the entire polymer substantially comprises at least one other comonomer, which is preferably an α-olefin having three or more carbon atoms.
[0047] As discussed, the ethylene / α-olefin multi-block interpolymers comprise two or more chemically distinct regions or segments (referred to as "blocks"), preferably linked in a linear fashion. In one embodiment, the blocks differ in the amount or type of comonomer incorporated, density, amount of crystallinity, crystallite size attributable to the polymer of such composition, type or degree of stereoisomerism (isotactic or syndiotactic), regioregularity or regioirregularity, amount of branching (including long chain branching or hyperbranching), uniformity, or any other chemical or physical characteristic. Compared to the block interpolymers of the prior art, including those produced by continuous monomer addition, stereolabile catalysts, or anionic polymerization techniques, the ethylene / α-olefin multi-block interpolymers of the present invention are characterized by a unique distribution of polymer polydispersity (PDI or Mw / Mn or MWD), polydisperse block length distribution, and / or polydisperse block number distribution, in one embodiment, due to the effect of one or more shuttling agents in combination with a variety of catalysts used in their preparation.
[0048] Ethylene / α-olefin multi-block interpolymers and further copolymers can generally be produced via a chain shuttling process, such as described, for example, in U.S. Pat. No. 7,858,706, which is incorporated herein by reference. Some chain shuttling agents and related information are listed in Column 16, Line 39 to Column 19, Line 44. Some catalysts are described in Column 19, Line 45 to Column 46, Line 19 and some cocatalysts are described in Column 46, Line 20 to Column 51, Line 28. Some process features are described in Column 51, Line 29 to Column 54, Line 56. See also the following: U.S. Pat. No. 7,608,668; U.S. Pat. No. 7,893,166; and U.S. Pat. No. 7,947,793 and U.S. Pat. No. 8,476,393. See also U.S. Pat. No. 9,243,173.
[0049] In one embodiment, the ethylene / α-olefin multi-block interpolymer (e.g., ethylene / octene multi-block interpolymer) is produced in a continuous process and has a polydispersity index (Mw / Mn) of 1.7 to 3.5, or 1.8 to 3, or 1.8 to 2.5, or 1.8 to 2.2. When prepared in a batch or semi-batch process, the ethylene / α-olefin multi-block interpolymer (e.g., ethylene / octene multi-block interpolymer) typically has a Mw / Mn of 1.0 to 3.5, or 1.3 to 3.0, or 1.4 to 2.5, or 1.4 to 2.0.
[0050] In addition, ethylene / α-olefin multi-block interpolymers (e.g., ethylene / octene multi-block interpolymers) typically have a PDI (or Mw / Mn) that fits a Schultz-Flory distribution rather than a Poisson distribution. In one embodiment, ethylene / α-olefin multi-block interpolymers (e.g., ethylene / octene multi-block interpolymers) have both a polydisperse block distribution and a polydisperse block size distribution. This results in the formation of a polymer product with improved and distinguishable physical properties. The theoretical benefits of a polydisperse block distribution have previously been modeled and discussed in Potemkin, Physical Review E (1998) 57 (6), pp. 6902-6912 and Dobrynin, J. Chem. Phys. (1997) 107 (21), pp. 9234-9238. In one embodiment, the ethylene / α-olefin multi-block interpolymer (ie, ethylene / octene multi-block interpolymer) has the most possible block length distribution.
[0051] definition
[0052] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.
[0053] As used herein, the term "composition" includes a mixture of materials that comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition. Any reaction products or decomposition products are typically present in trace or residual amounts.
[0054] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerizing monomers of the same or different types. Thus, the generic term polymer encompasses the term homopolymer (used to refer to polymers prepared from only one type of monomer, it being understood that trace amounts of impurities may be incorporated into the polymer structure) and the term interpolymer as defined below. Trace amounts of impurities (such as catalyst residues) may be incorporated into and / or within the polymer. Typically, the polymer is stabilized with very low amounts ("ppm" amounts) of one or more stabilizers, such as one or more antioxidants.
[0055] As used herein, the term "interpolymer" refers to polymers prepared by the polymerization of at least two different types of monomers. The term interpolymer thus encompasses the term copolymer (used to refer to polymers prepared from two different types of monomers) and polymers prepared from more than two different types of monomers.
[0056] As used herein, the term "olefin-based polymer" refers to polymers that contain, in polymerized form, 50 weight percent or majority weight percent of an olefin, such as ethylene or propylene (based on the weight of the polymer), and optionally may contain one or more comonomers.
[0057] As used herein, the term "propylene-based polymer" refers to a polymer that, in polymerized form, comprises a majority weight percent propylene (based on the weight of the polymer) and, optionally, may contain one or more comonomers.
[0058] As used herein, the term "ethylene-based polymer" refers to a polymer that, in polymerized form, contains 50 weight percent or majority weight percent ethylene (based on the weight of the polymer), and optionally may contain one or more comonomers.
[0059] As used herein, the term "ethylene / α-olefin interpolymer" refers to an interpolymer that contains, in polymerized form, 50 weight percent or a majority of weight percent ethylene (based on the weight of the interpolymer) and an α-olefin. The α-olefin is randomly distributed within the interpolymer. As used herein, the term "ethylene / α-olefin copolymer" refers to a copolymer that contains, in polymerized form, 50 weight percent or a majority of ethylene monomer (based on the weight of the copolymer) and an α-olefin as the only two monomer types. The α-olefin is randomly distributed within the copolymer.
[0060] As used herein, the term "ethylene / α-olefin multi-block interpolymer" refers to a multi-block interpolymer comprising 45 weight percent, and further 50 weight percent or a majority weight percent of ethylene (based on the weight of the interpolymer) and α-olefin in polymerized form. As used herein, the term "ethylene / α-olefin multi-block copolymer" refers to a multi-block copolymer comprising 45 weight percent, and further 50 weight percent or a majority weight percent of ethylene (based on the weight of the copolymer) and α-olefin as the only two monomer types in polymerized form. See also the previous discussion.
[0061] As used herein, the term "propylene homopolymer or polypropylene homopolymer" refers to a homopolymer comprising propylene as the monomer type in polymerized form.
[0062] As used herein, the phrase "majority weight percent" with respect to a polymer (or interpolymer or copolymer) refers to the amount of monomer that is present in the largest amount in the polymer.
[0063] As used herein, the terms "thermally treating," "thermally treated," "thermal treatment," and similar phrases with respect to inventive compositions as discussed herein refer to raising the temperature of the composition by the application of heat. As an example, the heat can be applied by an electrical device (e.g., a heating coil) and / or by radiation and / or by hot oil and / or by mechanical shearing. Note that the temperature at which the thermal treatment is performed refers to the temperature of the device "to which the heat is applied," or if the device contains an enclosed atmosphere or semi-enclosed atmosphere, the temperature of the atmosphere within the device, such as the atmosphere within an oven or tunnel (e.g., the air temperature in a hot air oven or hot air tunnel).
[0064] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequently recited component, step, or procedure, except those that are not essential to operability. The term "consisting of excludes any component, step, or procedure not specifically recited or listed.
[0065] List of some composition characteristics
[0066] A] A composition comprising a first composition, wherein the first composition comprises at least the following components a and b:
[0067] a) at least one ethylene / α-olefin multi-block interpolymer comprising a density of ≥ 0.870 g / cc and a soft segment melting temperature (SS-Tm) of ≤ 35°C;
[0068] b) A polymer composition comprising at least one propylene homopolymer and wherein the component a is present in an amount of ≤ 50 wt.-%, based on the weight of components a and b.
[0069] B] A composition according to A] above, wherein the ethylene / α-olefin multi-block interpolymer (of component a) has a density of ≥ 0.870 g / cc, or ≥ 0.871 g / cc, or ≥ 0.872 g / cc, or ≥ 0.873 g / cc, or ≥ 0.874 g / cc, or ≥ 0.875 g / cc, or ≥ 0.876 g / cc, or ≥ 0.877 g / cc, or ≥ 0.878 g / cc, or ≥ 0.879 g / cc, or ≥ 0.880 g / cc, or ≥ 0.881 g / cc, or ≥ 0.882 g / cc, or ≥ 0.883 g / cc, or ≥ 0.884 g / cc.
[0070] C] A composition according to A] or B] above, wherein the ethylene / α-olefin multi-block interpolymer (of component a) has a density of ≤0.910 g / cc, or ≤0.908 g / cc, or ≤0.906 g / cc, or ≤0.904 g / cc, or ≤0.902 g / cc, or ≤0.900 g / cc, or ≤0.898 g / cc, or ≤0.896 g / cc, or ≤0.894 g / cc, or ≤0.892 g / cc, or ≤0.890 g / cc, or ≤0.889 g / cc, or ≤0.888 g / cc, or ≤0.887 g / cc.
[0071] D] A composition according to any one of A]-C] (A] to C]) above, wherein the ethylene / α-olefin multi-block interpolymer (of component a) has a SS-Tm of ≤35°C, or ≤30°C, or ≤25°C, or ≤20°C, or ≤18°C, or ≤16°C, or ≤14°C, or ≤12°C, or ≤10°C, or ≤9°C, or ≤8°C, or ≤7°C, or ≤6°C.
[0072] E] A composition according to any one of A] to D] above, wherein the ethylene / α-olefin multi-block interpolymer (of component a) has a SS-Tm of ≥-20°C, or ≥-18°C, or ≥-16°C, or ≥-14°C, or ≥-12°C, or ≥-10°C, or ≥-8°C, ≥-6°C, or ≥-4°C, or ≥-2°C, or ≥-1°C, or ≥0°C, or ≥1°C, or ≥2°C, or ≥3°C, or ≥4°C.
[0073] F] A composition according to any one of A] to E] above, wherein component a has a density of ≥0.870 g / cc, or ≥0.871 g / cc, or ≥0.872 g / cc, or ≥0.873 g / cc, or ≥0.874 g / cc, or ≥0.875 g / cc, or ≥0.876 g / cc, or ≥0.877 g / cc, or ≥0.878 g / cc, or ≥0.879 g / cc, or ≥0.880 g / cc, or ≥0.881 g / cc, or ≥0.882 g / cc, or ≥0.883 g / cc, or ≥0.884 g / cc.
[0074] G] A composition according to any one of A] to F] above, wherein component a has a density of ≤0.910 g / cc, or ≤0.908 g / cc, or ≤0.906 g / cc, or ≤0.904 g / cc, or ≤0.902 g / cc, or ≤0.900 g / cc, or ≤0.898 g / cc, or ≤0.896 g / cc, or ≤0.894 g / cc, or ≤0.892 g / cc, or ≤0.890 g / cc, or ≤0.889 g / cc, or ≤0.888 g / cc, or ≤0.887 g / cc.
[0075] H] A composition according to any one of A] to G] above, wherein component a has a SS-Tm of ≤35°C, or ≤30°C, or ≤25°C, or ≤20°C, or ≤18°C, or ≤16°C, or ≤14°C, or ≤12°C, or ≤10°C, or ≤9°C, or ≤8°C, or ≤7°C, or ≤6°C.
[0076] I] A composition according to any one of A] to G] above, wherein component a has a SS-Tm of ≥-20°C, or ≥-18°C, ≥-16°C, or ≥-14°C, or ≥-12°C, or ≥-10°C, or ≥-8°C, ≥-6°C, or ≥-4°C, or ≥-2°C, or ≥-1°C, or ≥0°C, or ≥1°C, or ≥2°C, or ≥3°C, or ≥4°C.
[0077] J] A composition according to any one of A] to I] above, wherein the ethylene / α-olefin multi-block interpolymer (of component a) is an ethylene / α-olefin multi-block copolymer.
[0078] K] A composition according to any one of A] to J] above, wherein the α-olefin of the ethylene / α-olefin multi-block interpolymer is a C3-C20 α-olefin, and further a C3-C10 α-olefin, and further a C3-C8 α-olefin.
[0079] L] A composition according to any one of A] to K] above, wherein the ethylene / α-olefin multi-block interpolymer, and further copolymer, is selected from propylene, 1-butene, 1-pentene, 1-hexene or 1-octene, and further propylene, 1-butene or 1-octene, and further propylene or 1-octene, and further 1-octene.
[0080] M] A composition according to any one of A] to L] above, wherein the ethylene / α-olefin multi-block interpolymer (of component a) has ≥0.1 g / 10 min, or ≥0.2 g / 10 min, or ≥0.3 g / 10 min, or ≥0.4 g / 10 min, or ≥0.5 g / 10 min and / or ≤50 g / 10 min, or ≤45 g / 10 min, or ≤40 g / 10 min, or ≤35 g / 10 min, or ≤30 g / 10 min, or ≤28 g / 10 min, or ≤26 g / 10 min, or ≤24 g / 10 min, or ≤22 g / 10 min, or ≤20 g / 10 min, or ≤18 g / 10 min, or ≤16 g / 10 min, or ≤14 g / 10 min, or ≤12 g / 10 min, or ≤10 g / 10 min, or ≤9.0 g / 10 min, or ≤8.0 g / 10 min, or ≤7.0 g / 10 min, or ≤6.0 g / 10 min, or 5.0 g / 10 min melt index (MI or I2).
[0081] N] A composition according to any one of A] to M] above, wherein the ethylene / α-olefin multi-block interpolymer (of component a) has a molecular weight distribution (MWD=Mw / Mn) of ≥1.5, or ≥1.6, or ≥1.7, or ≥1.8, or ≥1.9, or ≥2.0 and / or ≤4.0, or ≤3.5, or ≤3.0, or ≤2.8, or ≤2.6, or ≤2.4.
[0082] O] A composition according to any one of A] to N] above, wherein the ethylene / α-olefin multi-block interpolymer (of component a) has a molecular weight distribution number average molecular weight (Mn) of ≥10000 g / mol, or ≥15000 g / mol, or ≥20000 g / mol, or ≥25000 g / mol, or ≥30000 g / mol, or ≥32000 g / mol, or ≥35000 g / mol and / or ≤100000, or ≤90000, or ≤80000, or ≤75000, or ≤70000, or ≤65000, or ≤60000.
[0083] P] A composition according to any one of A] to O] above, wherein the ethylene / α-olefin multi-block interpolymer (of component a) has a melting temperature (Tm) of ≥90°C, or ≥100°C, or ≥105°C, or ≥110°C, or ≥112°C, or ≥114°C, or ≥116°C, or ≥118°C and / or ≤140°C, or ≤135°C, or ≤130°C, or ≤128°C, or ≤126°C, or ≤124°C, or ≤123°C, as determined by DSC.
[0084] Q] A composition according to any one of A] to P] above, wherein the ethylene / α-olefin multi-block interpolymer (of component a) has a glass transition temperature (Tg) of ≥-75.0°C, or ≥-72.0°C, or ≥-70.0°C, or ≥-68.0°C, or ≥-66.0°C, or ≥-65.0°C and / or ≤-40.0°C, or ≤-50.0°C, or ≤-55.0°C, or ≤-60.0°C, as determined by DSC.
[0085] R] A composition according to any one of A] to Q] above, wherein component a comprises only one ethylene / α-olefin multi-block interpolymer, and further an ethylene / α-olefin multi-block copolymer.
[0086] S] A composition according to any one of A] to Q] above, wherein component a comprises only two ethylene / α-olefin multi-block interpolymers (first and second), and further two ethylene / α-olefin multi-block copolymers.
[0087] T] The composition according to S] above, wherein the first interpolymer, and further the melt index (MI) of the copolymer 1 ) is greater than the second interpolymer, and further the melt index (MI) of the copolymer 2 ).
[0088] U] A composition according to S] or T] above, wherein the ratio MI 1 / MI 2 It is ≥2.0g / 10min, or ≥3.0g / 10min, or ≥3.5g / 10min, or ≥4.0g / 10min, or ≥4.5g / 10min, or ≥5.0g / 10min and / or ≤20g / 10min, or ≤15g / 10min, or ≤10g / 10min, or ≤6.0g / 10min.
[0089] V] A composition according to any of S] - U] above, wherein the ratio of the density of the first interpolymer, further copolymer to the density of the second interpolymer, further copolymer is ≥ 0.850, or ≥ 0.900, or ≥ 0.950, or ≥ 1.00 and / or ≤ 1.20, or ≤ 1.15, or ≤ 1.10, or ≤ 1.05.
[0090] W] A composition according to any one of S] to V] above, wherein the weight ratio of the first interpolymer, further copolymer to the second interpolymer, further copolymer is ≥0.40, or ≥0.60, or ≥0.80, or ≥1.0 and / or ≤3.0, or ≤2.0, or ≤1.8, or ≤1.6, or ≤1.4, or ≤1.2.
[0091] X] A composition according to any one of S] to W] above, wherein the α-olefin of each ethylene / α-olefin multi-block interpolymer, and further the copolymer is independently a C3-C20 α-olefin, and further a C3-C10 α-olefin, and further a C3-C8 α-olefin.
[0092] Y] A composition according to S] or X] above, wherein the α-olefin of each ethylene / α-olefin multi-block interpolymer, and further the copolymer, is independently selected from propylene, 1-butene, 1-pentene, 1-hexene or 1-octene, and further propylene, 1-butene or 1-octene, and further propylene or 1-octene, and further 1-octene.
[0093] Z] A composition according to any of S] to Y] above, wherein the α-olefin of the first interpolymer, further copolymer is the same as the α-olefin of the second interpolymer, further copolymer.
[0094] A2] The composition according to any one of S] to Z] above, wherein component a comprises ≥ 95 wt%, or ≥ 98 wt%, or ≥ 99 wt% to ≤ 100 wt% of the first and second interpolymers, and further the first and second copolymers.
[0095] B2] A composition according to any one of A] to A2] above, wherein component a has a cumulative crystallinity change % satisfying the following relationship: [(cumulative crystallinity % at room temperature (23°C))-(cumulative crystallinity % at 60°C)]≤10%, or ≤8.0%, or ≤6.0%, or ≤5.0%, or ≤4.0%, or ≤3.0%, or ≤2.0%. The cumulative crystallinity % is determined by DSC as described herein.
[0096] C2] A composition according to any one of A] to B2] above, wherein the propylene homopolymer (of component b) has a melt flow rate (MFR) of ≥1.0 g / 10 min, or ≥2.0 g / 10 min, or ≥3.0 g / 10 min, or ≥4.0 g / 10 min, or ≥5.0 g / 10 min, or ≥10 g / 10 min, or ≥20 g / 10 min, or ≥25 g / 10 min and / or ≤200 g / 10 min, or ≤150 g / 10 min, or ≤100 g / 10 min, or ≤90 g / 10 min, or ≤80 g / 10 min, or ≤75 g / 10 min, or ≤70 g / 10 min, or ≤68 g / 10 min, or ≤66 g / 10 min.
[0097] D2] A composition according to any one of A] to C2] above, wherein the propylene homopolymer (of component b) has a density of ≥0.875 g / cc, or ≥0.880 g / cc, or ≥0.885 g / cc, or ≥0.890 g / cc, or ≥0.895 g / cc, or ≥0.900 g / cc and / or ≤0.935 g / cc, or ≤0.930 g / cc, or ≤0.925 g / cc, or ≤0.920 g / cc, or ≤0.915 g / cc, or ≤0.910 g / cc.
[0098] E2] A composition according to any one of A] to D2] above, wherein component b has a melt flow rate (MFR) of ≥1.0 g / 10 min, or ≥2.0 g / 10 min, or ≥3.0 g / 10 min, or ≥4.0 g / 10 min, or ≥5.0 g / 10 min, or ≥10 g / 10 min, or ≥20 g / 10 min, or ≥25 g / 10 min and / or ≤200 g / 10 min, or ≤150 g / 10 min, or ≤100 g / 10 min, or ≤90 g / 10 min, or ≤80 g / 10 min, or ≤75 g / 10 min, or ≤70 g / 10 min, or ≤68 g / 10 min, or ≤66 g / 10 min.
[0099] F2] A composition according to any one of A] to E2] above, wherein component b has a density of ≥0.875 g / cc, or ≥0.880 g / cc, or ≥0.885 g / cc, or ≥0.890 g / cc, or ≥0.895 g / cc, or ≥0.900 g / cc and / or ≤0.935 g / cc, or ≤0.930 g / cc, or ≤0.925 g / cc, or ≤0.920 g / cc, or ≤0.915 g / cc, or ≤0.910 g / cc.
[0100] G2] A composition according to any one of A] to F2] above, wherein component b comprises at least two propylene homopolymers (first and second), and further two propylene homopolymers (first and second).
[0101] H2] The composition according to G2] above, wherein the melt flow rate (MFR hPP1 ) is greater than the melt flow rate (MFR) of the second homopolymer hPP2 ).
[0102] I2] A composition according to G2] or H2] above, wherein the melt flow rate (MFR hPP1 ) is ≥10g / 10min, or ≥20g / 10min, or ≥40g / 10min, or ≥60g / 10min, or ≥80g / 10min, or ≥100g / 10min and / or ≤1000g / 10min, or ≤800g / 10min, or ≤600g / 10min, or ≤400g / 10min, or ≤300g / 10min, or ≤200g / 10min, or ≤150g / 10min, or ≤120g / 10min.
[0103] J2] A composition according to any one of G2] to I2] above, wherein the MFR hPP1 / MFR hPP2 The ratio is >1.0, or ≥2.0, or ≥5.0, or ≥7.0, or ≥10 and / or ≤50, or ≤45, or ≤40, or ≤35, or ≤30.
[0104] K2] A composition according to any one of G2] to J2] above, wherein the ratio of the density of the first propylene homopolymer to the density of the second propylene homopolymer is ≥0.800, or ≥0.850, or ≥0.900, or ≥0.950, or ≥1.00 and / or ≤1.30, or ≤1.25, or ≤1.20, or ≤1.15, or ≤1.10, or ≤1.05.
[0105] L2] A composition according to any one of G2] to K2] above, wherein the weight ratio of the first propylene homopolymer to the second propylene homopolymer is ≥0.10, or ≥0.20, or ≥0.40, or ≥0.50, or ≥0.60, or ≥0.80, or ≥1.0, or ≥1.2, or ≥1.4, or ≥1.5 and / or ≤10, or ≤8.0, or ≤6.0, or ≤4.0, or ≤2.0, or ≤1.8, or ≤1.6.
[0106] M2] A composition according to any of G2] to L2] above, wherein component b comprises ≥ 95 wt%, or ≥ 98 wt%, or ≥ 99 wt% to ≤ 100 wt% of the first and second propylene homopolymers.
[0107] N2] A composition according to any one of A] to M2] above, wherein the weight ratio of component b to component a is ≥1.0, or ≥1.2, or ≥1.4, or ≥1.6, or ≥1.8 and / or ≤10, or ≤9.0, or ≤8.0, ≤7.0, or ≤6.0, or ≤5.5, or ≤5.0, or ≤4.5, or ≤4.0, or ≤3.5, or ≤3.0.
[0108] O2] A composition according to any one of A] to N2] above, wherein the ratio of the MFR of component b to the I2 of component a is ≥0.4, or ≥1.0, or ≥1.5, or ≥2.0, or ≥3.0 and / or ≤230, or ≤200, or ≤100, or ≤50, or ≤20, or ≤10.
[0109] P2] A composition according to any one of A] to O2] above, wherein the ratio of the density of component b to the density of component a is ≥0.98, or ≥0.99, or ≥1.00, or ≥1.01 and / or ≤1.20, or ≤1.15, or ≤1.10, or ≤1.08, or ≤1.06, or ≤1.05.
[0110] Q2] A composition according to any one of A] to P2] above, wherein the first composition comprises ≥10 wt%, or ≥15 wt%, or ≥20 wt%, or ≥22 wt%, or ≥25 wt% of component a and / or ≤50 wt%, or ≤40 wt%, or ≤38 wt%, or ≤32 wt%, or ≤30 wt%, or ≤28 wt% of component a, based on the total weight of components a and b.
[0111] R2] A composition according to any one of A] to Q2] above, wherein the first composition comprises ≥15 wt%, or ≥20 wt%, or ≥30 wt%, or ≥40 wt%, or ≥50 wt%, or ≥55 wt%, or ≥60 wt%, or ≥62 wt%, or ≥65 wt%, or ≥68 wt% of component b and / or ≤80 wt%, or ≤78 wt%, or ≤75 wt% of component b, based on the total weight of components a and b.
[0112] S2] A composition according to any one of A] to R2] above, wherein the first composition comprises components a and b in a total amount of ≥80 wt%, or ≥85 wt%, or ≥90 wt%, or ≥92 wt%, or ≥94 wt%, or ≥96 wt%, or ≥98 wt%, based on the weight of the first composition.
[0113] T2] A composition according to any one of A] to S2] above, wherein the first composition comprises components a and b in an amount of ≤100 wt% or ≤99 wt% based on the weight of the first composition.
[0114] U2] A composition according to any one of A] to T2] above, wherein the first composition comprises at least two crystallization peaks (a first peak and a second peak), and wherein the second peak and the first peak are peaks having the highest and second highest crystallization temperatures, respectively.
[0115] V2] The composition according to U2] above, wherein the second peak and the first peak each independently have a crystallization temperature of ≥ 100°C.
[0116] W2] A composition according to U2] or V2] above, wherein the first crystallization peak has a crystallization temperature (peak temperature) of ≥100°C, or ≥102°C, or ≥104°C, or ≥106°C, or ≥108°C, or ≥110°C, or ≥116°C, or ≥112°C, or ≥114°C, or ≥116°C and / or ≤140°C, or ≤138°C, or ≤138°C, ≤134°C, or ≤132°C, or ≤130°C, or ≤128°C, or ≤126°C, or ≤124°C.
[0117] X2] A composition according to any one of U2] to W2] above, wherein the second crystallization peak has a crystallization temperature (peak temperature) of ≥106°C, or ≥108°C, or ≥110°C, or ≥112°C, or ≥114°C, or ≥116°C, or ≥118°C, or ≥120°C, or ≥122°C, or ≥124°C, or ≥126°C, or ≥128°C, or ≥130°C and / or ≤160°C, or ≤155°C, or ≤150°C, ≤148°C, or ≥146°C, or ≥144°C, or ≤142°C, or ≤140°C, or ≤138°C, or ≥136°C, or ≥134°C.
[0118] Y2] A composition according to any one of U2] to X2] above, wherein the composition has a crystallization temperature that is ≥5°C, or ≥7°C, or ≥10°C, or ≥12°C, or ≥14°C, or ≥16°C, or ≥18°C, or ≥20°C, or ≥22°C, or ≥25°C, or ≥27°C, or ≥30°C, or ≥32°C, or ≥35°C, or ≥37°C, or ≥40°C, or ≥42°C, or ≥45°C, or ≥47°C, or ≥50°C and / or ≤90°C, or ≤80°C, or ≤70°C higher than the crystallization temperature of the first crystallization peak.
[0119] Z2] A composition according to any one of U2] to Y2] above, wherein the first crystallization peak and the second crystallization peak appear as two separate peaks on the DSC curve, and the two peaks do not overlap.
[0120] A3] A composition according to any one of U2] to Z2] above, wherein the intensity (in Watts / g) of each of the first crystallization peak and the second crystallization peak independently satisfies the following relationship: [(peak intensity)-(average baseline intensity)]≤-0.05 Watts / g, further ≤-0.10 Watts / g, further ≤-0.15 Watts / g, further ≤-0.20 Watts / g, further ≤-0.25 Watts / g, further ≤-0.30 Watts / g, further ≤-0.35 Watts / g. "Average baseline intensity (in Watts / g)" = [(heat flow (Watts / g) at 160°C) - (heat flow (Watts / g) at -40°C)] / 2.
[0121] B3] A composition according to any one of A] to A3] above, wherein the first composition comprises components a and b as the only polymer components of the first composition.
[0122] C3] A composition according to any one of A] to B3] above, wherein the composition comprises ≥55 wt%, or ≥60 wt%, or ≥65 wt%, or ≥70 wt%, or ≥75 wt% of component b, based on the weight of the composition and / or ≤90 wt%, or ≤85 wt%, or ≤80 wt% of component b, based on the weight of the composition.
[0123] D3] A composition according to any one of A] to C3] above, wherein the composition comprises ≤45 wt%, or ≤40 wt%, or ≤35 wt%, or ≤30 wt%, or ≤25 wt%, or ≤20 wt% of component b, based on the weight of the composition and / or ≥5.0 wt%, or ≥10 wt%, or ≥15 wt% of component a, based on the weight of the composition.
[0124] E3] A composition according to any one of A] to D3] above, wherein the composition comprises components a and b in a total amount of ≥50 wt%, or ≥60 wt%, ≥70 wt%, or ≥80 wt%, or ≥85 wt%, or ≥90 wt%, or ≥95 wt%, based on the weight of the composition and / or components a and b in a total amount of ≤100 wt%, or ≤99 wt%, ≤98 wt%, or ≤97 wt%, based on the weight of the composition.
[0125] F3] A composition according to any one of A] to E3] above, wherein the composition comprises ≥50 wt.%, or ≥60 wt.%, ≥70 wt.%, or ≥80 wt.%, or ≥85 wt.%, or ≥90 wt.%, or ≥95 wt.%, or ≥96 wt.%, or ≥97 wt.% of the first composition, based on the weight of the composition, and / or ≤100 wt.%, or ≤99 wt.%, or ≤98 wt.% of the first composition, based on the weight of the composition.
[0126] G3] A composition according to any one of A] to F3] above, wherein the composition further comprises at least one additive.
[0127] H3] A composition according to G3] above, wherein the at least one additive is selected from fillers (e.g., talc and nanoclay), glidants, antioxidants, colorants, processing aids (e.g., zinc stearate), lubricants or any combination thereof.
[0128] I3] A composition according to G3] or H3] above, wherein the composition further comprises at least one filler (eg, talc and nanoclay).
[0129] J3] A composition according to I3] above, wherein the composition comprises ≥0.5 wt%, or 1.0 wt%, or ≥2.0 wt%, or ≥3.0 wt%, or ≥4.0 wt%, or ≥5.0 wt% of the at least one filler and / or ≤40 wt%, or ≤35 wt%, or ≤30 wt%, or ≤25 wt%, or ≤20 wt%, or ≤15 wt%, or ≤10 wt%, or ≤8.0 wt% of the at least one filler, based on the weight of the composition.
[0130] K3] A composition according to G3] or H3] above, wherein the at least one additive is present in an amount of ≥0.01 wt%, or ≥0.02 wt%, or ≥0.05 wt%, or ≥0.10 wt%, or ≥0.20 wt%, or ≥0.50 wt% and / or ≤10 wt%, or ≤5.0 wt%, or ≤2.0 wt%, or ≤1.0 wt%, based on the weight of the composition.
[0131] L3] A composition according to any one of A] to K3] above, wherein the composition further comprises a polymer which is independently different from each of component a and component b in one or more characteristics (such as monomer type, monomer distribution, monomer amount, density, melt index (I2) or melt flow rate (MFR), Mn, MWD or any combination thereof), and further in one or more characteristics (such as monomer type, monomer distribution, monomer amount, density, melt index (I2) or melt flow rate (MFR) or any combination thereof).
[0132] M3] A composition according to any one of A] to L3] above, wherein the composition comprises ≤5.0 wt%, or ≤2.0 wt%, or ≤1.0 wt%, or ≤0.5 wt%, or ≤0.2 wt%, or ≤0.1 wt%, or ≤0.05 wt% of an amide compound (e.g., fatty amide), based on the weight of the composition; and further the composition does not comprise an amide compound.
[0133] N3] A composition according to any one of A] to M3] above, wherein the composition comprises ≤5.0 wt%, or ≤2.0 wt%, or ≤1.0 wt%, or ≤0.5 wt%, or ≤0.2 wt%, or ≤0.1 wt%, or ≤0.05 wt% of polyamide based on the weight of the composition; and further the composition does not comprise polyamide.
[0134] O3] A composition according to any one of A]-N3] above, wherein the composition comprises ≤5.0 wt%, or ≤2.0 wt%, or ≤1.0 wt%, or ≤0.5 wt%, or ≤0.2 wt%, or ≤0.1 wt%, or ≤0.05 wt% of ethylene-vinyl acetate (EVA) polymer based on the weight of the composition; and further the composition does not comprise ethylene-vinyl acetate (EVA) polymer.
[0135] P3] A composition according to any one of A] to O3] above, wherein the composition comprises ≤5.0 wt%, or ≤2.0 wt%, or ≤1.0 wt%, or ≤0.5 wt%, or ≤0.2 wt%, or ≤0.1 wt%, or ≤0.05 wt% of a metal hydroxide (e.g., magnesium hydroxide), based on the weight of the composition; and further the composition does not comprise a metal hydroxide.
[0136] Q3] A composition according to any one of A] to P3] above, wherein the composition comprises ≤5.0 wt%, or ≤2.0 wt%, or ≤1.0 wt%, or ≤0.5 wt%, or ≤0.2 wt%, or ≤0.1 wt%, or ≤0.05 wt% of wax based on the weight of the composition; and further the composition does not contain wax.
[0137] R3] A composition according to any one of A] to Q3] above, wherein the composition comprises ≤5.0 wt%, or ≤2.0 wt%, or ≤1.0 wt%, or ≤0.5 wt%, or ≤0.2 wt%, or ≤0.1 wt%, or ≤0.05 wt% of a tackifier based on the weight of the composition; and further the composition does not comprise a tackifier.
[0138] S3] A composition according to any one of A] to R3] above, wherein the composition has an MFR of ≥5.0 g / 10 min, or ≥7.0 g / 10 min, or ≥10 g / 10 min, or ≥12 g / 10 min, or ≥15 g / 10 min, or ≥18 g / 10 min, or ≥20 g / 10 min and / or ≤50 g / 10 min, or ≤45 g / 10 min, or ≤40 g / 10 min, or ≤35 g / 10 min, or ≤30 g / 10 min, or ≤25 g / 10 min.
[0139] T3] A composition according to any one of A] to S3] above, wherein the light transmittance (3.2 mm thickness) of the composition at room temperature (23° C.) is ≥30%, or ≥35%, or ≥40%, or ≥45%, or ≥50%, or ≥55%, or ≥60% and / or ≤100%, or ≤95%. The light transmittance is determined as described herein.
[0140] U3] A composition according to any one of A] to T3] above, wherein the transmittance of the composition at 40°C (3.2 mm thickness) is ≥30%, or ≥35%, or ≥40%, or ≥45%, or ≥50%, or ≥55%, or ≥60% and / or ≤100%, or ≤95%.
[0141] V3] A composition according to any one of A] to U3] above, wherein the transmittance of the composition at 60°C (3.2 mm thickness) is ≥30%, or ≥35%, or ≥40%, or ≥45%, or ≥50%, or ≥55%, or ≥60% and / or ≤100%, or ≤95%.
[0142] W3] A composition according to any one of A] to V3] above, wherein the composition has a transmittance change % that satisfies the following relationship: [(transmittance (3.2 mm thickness) at room temperature (23°C))-(transmittance (3.2 mm thickness) at 60°C)]≤15%, or ≤14%, or ≤13%, or ≤12%, or ≤11%, or ≤10%, or ≤9.0%, or ≤8.0%, or ≤7.0%, or ≤6.0%, or ≤5.0%.
[0143] X3] A composition according to any one of A] to W3] above, wherein the composition has a dart ductility (2.2 m / s) at -40°C of ≥ 90%, or ≥ 95%, or ≥ 100%. The dart ductility is as described herein.
[0144] Y3] A composition according to any one of A] to X3] above, wherein the dart ductility (2.2 m / s) of the composition at -30°C is ≥90%, or ≥95%, or ≥100%.
[0145] Z3] A composition according to any one of A] to Y3] above, wherein the dart ductility (2.2 m / s) of the composition at -20°C is ≥90%, or ≥95%, or ≥100%.
[0146] A4] The composition according to any one of A] to Z3] above, wherein the dart ductility (2.2 m / s) of the composition at -10°C is ≥90%, or ≥95%, or ≥100%.
[0147] B4] A composition according to any one of A] to A4] above, wherein the dart ductility (2.2 m / s) of the composition at 0°C is ≥90%, or ≥95%, or ≥100%.
[0148] C4] A composition according to any one of A] to B4] above, wherein the composition has a notched Izod beam of ≥3 kJ / m at -30°C. 2 , or ≥4kJ / m 2 , or ≥5kJ / m 2 , or ≥6kJ / m 2 , or ≥7 kJ / m 2 , ≥8kJ / m 2 , or ≥9kJ / m 2 , or ≥10kJ / m 2 The cantilever notch is described in this article.
[0149] D4] A composition according to any one of A] to C4] above, wherein the composition has a notched Izod beam of ≥5 kJ / m at 0°C. 2 , or ≥10kJ / m 2 , or ≥15kJ / m 2 , or ≥20kJ / m 2 , or ≥25kJ / m 2 , or ≥30kJ / m 2 .
[0150] E4] A composition according to any one of A] to D4] above, wherein the composition has an Izod notch at 23°C or ≥10 kJ / m 2 , or ≥15kJ / m 2 , or ≥20kJ / m 2 , or ≥25kJ / m 2 , or ≥30kJ / m 2 , or ≥35kJ / m 2 , or ≥40kJ / m 2 , or ≥45kJ / m 2 , or ≥50kJ / m 2 .
[0151] F4] The composition according to any one of A] to E4] above, wherein the composition has a flexural modulus of ≥800 MPa, or ≥900 MPa, or ≥1000 MPa. Flexural modulus is described herein.
[0152] G4] A composition according to any one of A] to F4] above, wherein the composition has good light diffusion properties, such as Figure 3 See the Experimental section for definitions and tests.
[0153] H4] An article comprising at least one component formed from the composition according to any one of A] to G4] above.
[0154] I4] The article according to H4] above, wherein the article is an automobile part.
[0155] J4] A method of forming an automotive part, the method comprising mixing a composition according to any one of A] to G4] above, and further heat treating the composition.
[0156] Test Method
[0157] The melt index or melt flow rate of a polymer
[0158] The melt index MI (or I2) of ethylene-based polymers or compositions is measured at 190°C / 2.16kg according to ASTM D-1238. The melt flow rate MFR of propylene-based polymers or compositions is measured at 230°C / 2.16kg according to ASTM D-1238.
[0159] density
[0160] The density of the polymer was measured according to ASTM D792, where the test apparatus was not annealed (annealing step was skipped), using a balance and an isopropanol bath. Each sample was first compression molded at 190°C, 3000 lbs for 6 minutes, then compression molded at 25000 lbs for 4 minutes, and then cooled at 15°C / min until the sample cooled to 30°C. After compression molding, the density of the polymer sample was measured in an isopropanol bath (temperature controlled at 23°C + / - 0.2°C) within 1 hour. The results are expressed in grams per cubic centimeter (g / cc = g / cm 3 )Record.
[0161] Differential Scanning Calorimetry (DSC) and Determination of SS-Tm of Ethylene / α-olefin Multi-block Interpolymers; and Compositions DSC of (TPO)
[0162] Differential scanning calorimetry (DSC) can be used to measure the melting, crystallization and glass transition behavior of polymers over a wide temperature range. For example, a TA Instruments Discovery DSC equipped with a refrigerated cooling system (RCS) and an automatic sampler is used to perform this analysis. During the test, a nitrogen purge gas flow of 50ml / min is used. Each sample is melt pressed (preheated for 2 minutes, and pressed for 2 minutes under a pressure of 10MPa) into a film at about 190°C. The molten sample is then air cooled to room temperature (about 23-25°C). A "3mg-10mg" 6mm diameter sample is extracted from the cooled polymer, weighed, placed in a light aluminum pan (about 50mg), and crimped closed. Analysis is then performed to determine its thermal properties.
[0163] The thermal behavior of the sample is determined by ramping the sample temperature up and down to produce a "heat flow versus temperature" curve. First, the sample is quickly heated to 180°C (for POE) or 230°C (for TPO (composition)) and kept isothermal for 5 minutes to remove its thermal history. Next, the sample is cooled to -90°C at a cooling rate of 10°C / minute and kept isothermal at -90°C for 5 minutes. The sample is then heated to 180°C (for POE) and 230°C (for TPO (composition)) at a heating rate of 10°C / minute (this is the "second heating" ramp). The cooling curve and the second heating curve are recorded.
[0164] The glass transition temperature Tg is determined by the DSC second heating curve in which half of the sample has obtained the liquid heat capacity, such as Bernhard Wunderlich, The Basis of Thermal Analysis, in Thermal Characterization of Polymeric Materials, 92, 278-279 (Edith A. Turi ed., 2nd edition, 1997). Baselines are drawn from below and above the glass transition zone and extrapolated through the Tg zone. The temperature at the midpoint between these baselines is the Tg of the sample heat capacity. The melting point Tm of the polymer sample is determined as the temperature corresponding to the maximum heat flow (absorption) in the second DSC heating curve. The crystallization temperature of the polymer sample is determined as the temperature corresponding to the maximum exothermic temperature in the DSC cooling curve (or the temperature (peak temperature) of the crystallization peak corresponding to the lowest decline of the exothermic peak). By dividing the heat of fusion (H) determined from the second heating curve f ) divided by the theoretical heat of fusion for an ethylene-based polymer sample (e.g., 292 J / g) and multiplying this number by 100 to calculate the percent crystallinity (e.g., for an ethylene-based polymer sample, % Crystallinity = (H f / 292J / g)×100).
[0165] By first calculating the sample at T s and 140°C. s ) to determine the specific temperature ( Ts ) is the cumulative crystallinity. In this case, the second heating curve is baseline corrected by drawing a linear baseline between the heat flows at -50 °C and 140 °C. The linear baseline can then be obtained from the heat flows at two temperature points (i.e., T s and 140°C) by integrating the baseline-corrected heat flow curves to calculate H s Then, by adding H s Divide by the theoretical heat of fusion of PE of 292 J / g and multiply this number by 100 to calculate the melting point at a specific temperature (T s ) of the cumulative crystallinity (e.g., the cumulative crystallinity % (at T s )=(Hs / 292J / g)×100(for PE)). Then the change in crystallinity of POE between room temperature and 60°C is calculated as s = The cumulative crystallinity at 23°C and at T s =The difference in cumulative crystallinity at 60°C.
[0166] The soft segment melting temperature SS-Tm is determined by the DSC second heating curve. For example, ethylene / octene multi-block copolymers generally have two melting peaks, one melting peak associated with the soft segment and one melting point associated with the hard segment. SS-Tm is associated with the lower temperature peak of the soft segment. For some block copolymers, the peak associated with the melting of the soft segment is a small peak (or protrusion) on the baseline, making it difficult to assign the maximum peak. This difficulty can be overcome by converting a normal DSC curve into a weighted DSC curve using the following method.
[0167] In DSC, the heat flow depends on the amount of material that melts at a specific temperature and the temperature-dependent specific heat capacity. The temperature dependence of the specific heat capacity in the molten state of linear low-density polyethylene causes the heat of fusion to increase with decreasing comonomer content. That is, as the comonomer content increases, the crystallinity decreases and the heat of fusion value gradually decreases. See Wild, L. Chang, S. and Shankernarayanan, M J., Improved Method for Compositional Analysis of Polyolefins by DSC, Polym. Prep 1990; 31: 270-1, which is incorporated herein by reference in its entirety. For a given point in a DSC curve (defined by heat flow in watts / gram (W / g) and temperature in degrees Celsius), the DSC curve can be converted into a weight-dependent distribution curve by taking the ratio of the "heat of fusion associated with temperature (ΔH(T))" to the "expected heat of fusion of the linear copolymer", as discussed below.
[0168] For DSC analysis of the composition, the second heating curve is baseline corrected, for example, by drawing a linear baseline between the heat flows at -50°C and 135°C. A temperature-dependent heat of melting curve (or "enthalpy (J / g) versus temperature (°C)") can then be generated from the sum of the integrated heat flows between two consecutive data points (from the "heat flow (W / g) versus time (min)" curve). The sum is generally represented by a cumulative enthalpy curve ("enthalpy (J / g) versus temperature (°C)" curve). Note that Joule (J) = Watt (W) * second, and that each temperature is determined by a corresponding time point and temperature ramp.
[0169] The expected relationship between the heat of fusion of linear ethylene / octene copolymers at a given temperature is shown by the "heat of fusion versus melting temperature" curve. By using random ethylene / octene copolymers, the expected heat of fusion ΔH for linear copolymers can be obtained. 线性共聚物 and the melting temperature Tm (in ° C) as follows (calibration equation): See also Figure 1 ("Melting Enthalpy (J / g) versus Melting Temperature (°C)" for linear copolymers).
[0170] For each integrated data point from the cumulative enthalpy curve ("Enthalpy (J / g) vs. Temperature (°C)" curve) at a given temperature (T), the ratio of the "enthalpy from the cumulative enthalpy curve to the expected heat of fusion for a linear copolymer at that temperature" yields a fractional weight that can be assigned to the corresponding data point. Thus, DSC weight fraction = [Cumulative enthalpy from calibration equation (at T) / melting enthalpy (at T)]. Using this ratio, a plot of DSC weight fraction vs. temperature (°C) can be generated, and the area under the curve (or A) can be calculated. 总和 ). The DSC weight fraction can be divided by A 总和 (or DSC weight fraction / A 总和 ) to calculate the normalized DSC weight fraction at each T. Thus, a normalized DSC weight fraction versus temperature (°C) curve can be generated. The soft segment Tm (SS-Tm) is assigned to the temperature at the maximum position in the normalized DSC weight fraction versus temperature (°C) curve. This method is applicable to copolymers containing polymerized ethylene and polymerized octene, but can also be applied to other polymers.
[0171] Cantilever beam notch strength, kJ / m 2 (-30℃, 0℃ and 23℃)
[0172] The Izod notch test is performed according to ASTM D256. Each test sample is punched out from an injection molded Type I tensile test bar with a final size of "2.5 inches x 0.5 inches x 0.125 inches". The sample is notched in the center along the length of the sample in the thickness direction using an automatic notcher with a depth of 0.1 inches. The notch half angle is 22.5° and the radius of curvature at the top is 0.01 inches. The samples are conditioned at 23+ / -2°C and 50+ / -10% relative humidity for at least 40 hours. For samples tested at non-ambient temperatures (-30°C and 0°C), each test sample is further conditioned at the test temperature for at least one hour. In this article, the test is performed on three temperature samples (-30°C, 0°C and 23°C), and for each temperature, five test samples (each composition) are tested and the average value is reported.
[0173] Notched Charpy, kJ / m 2 (-30℃ and 23℃)
[0174] This test is based on ISO 179 for determining Charpy impact properties. It calculates the impact energy absorbed by the sample after windage and friction losses have been automatically determined. 10 specimens are punched out from ISO injection moulded strips of 4 mm thickness. The specimens are 80 mm long and 10 mm wide. The specimens are notched in the thickness direction in the centre along the length of the specimen using an automatic notcher. The samples are conditioned at 23 + / - 2°C and 50 + / - 10% relative humidity for at least 40 hours. For samples tested at non-ambient temperature (i.e. -30°C), each test sample is further conditioned at the test temperature for a minimum of one hour.
[0175] Flexural modulus
[0176] According to ASTM D790, the flexural modulus was measured using an injection molded I-type tensile test bar and an INSTRON testing machine. A test speed of 0.05 inches / min was selected. Five test samples (each composition) were measured and the average value was recorded. The tangent modulus of elasticity described in ASTM D790 was reported as the flexural modulus of the composition.
[0177] Multi-axis dart impact (dart ductility)
[0178] Each composition was subjected to a multi-axis dart drop test on an Instron CEAST 9350 drop tower impact system (DYNATUP) according to ASTM D3763. The test was run at 2.2 m / s, equivalent to 5 miles per hour, a standard rate for the automotive industry. The sample temperature was carefully controlled. The samples were placed in a freezing unit with a controlled temperature of + / - 2°C for a minimum of 4 hours. The impact test was carried out in a temperature controlled room with a controlled temperature of + / - 2°C. In the present case, the samples were tested at -20°C, -30°C and -40°C. The samples (discs with a thickness of 3.2 mm) may break in ductile, semi-ductile or brittle modes. The mode was determined by visual inspection of the impacted discs. See, e.g. Figure 2 . Semi-brittle (C) samples had cracks but no chips missing (score 0.5), and brittle (B) samples had chips missing from the disk (score 0). Ductile (D) samples had only a hole in the center of the disk (score 1). The % ductility for each composition was calculated as the total score for each batch tested divided by the total number of samples in the batch (at least 5). Throughout this document, the lowest temperature with 100% dart drop ductility is reported (out of the three tested temperatures), or the average % ductility at each temperature is reported.
[0179] Transmittance %
[0180] According to ASTM D1003, the transmittance of each composition was measured from an injection molded disc with a thickness of 3.2 mm using Haze-Gard Plus (BYK Instruments). This method measures transmittance by the ratio of the luminous flux through an object to the flux incident on the object. The reported value is the percentage (%) of the flux (light) transmitted. For the transmittance at room temperature, the measurement was performed without any prior sample treatment. For the transmittance at 40°C and 60°C, the test samples were stored in ovens set to 40°C and 60°C for 2 hours, respectively, and the measurement was performed immediately. For each composition, the transmittance obtained at each temperature is the average value of at least 3 (usually 3 to 5) independent measurements.
[0181] Gel Permeation Chromatography (GPC) - Ethylene-based Polymers
[0182] The chromatographic system consists of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven compartment is set at 160°C and the column compartment is set at 150°C. The columns are four AGILENT "Mixed A" 30cm20 micron linear mixed bed columns. The chromatographic solvent is 1,2,4-trichlorobenzene containing 200ppm of butylated hydroxytoluene (BHT). The solvent source is nitrogen bubbled. The injection volume is 200 microliters and the flow rate is 1.0 ml / min.
[0183] The GPC column set was calibrated with 21 narrow molecular weight distribution polystyrene standards ranging from 580 to 8,400,000 molecular weights and arranged in six "cocktail" mixtures with at least ten times intervals between individual molecular weights. These standards were purchased from Agilent Technologies. For molecular weights equal to or greater than 1,000,000, "0.025 grams" of polystyrene standards were prepared in 50 milliliters of solvent, and for molecular weights less than 1,000,000, "0.05 grams" of polystyrene standards were prepared in 50 milliliters of solvent. The polystyrene standards were dissolved by gentle stirring at 80°C for 30 minutes. The polystyrene standard peak molecular weights were converted to polyethylene molecular weights using Equation 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)):
[0184] M 聚乙烯 =A×(M 聚乙烯 ) B (Equation 1), where M is the molecular weight, A has a value of 0.4315, and B equals 1.0.
[0185] A fifth order polynomial was used to fit the calibration points to the corresponding polyethylene equivalents.A small adjustment (approximately 0.375 to 0.445) was made to A to correct for column resolution and band broadening effects such that a linear homopolymer polyethylene standard was obtained at 120,000 Mw.
[0186] Total plate counts for the GPC column set were performed using decane (prepared as 0.04 g in 50 mL TCB and dissolved for 20 minutes with slow stirring). Plate counts (Equation 2) and symmetry (Equation 3) were measured with 200 microliter injections according to the following equations:
[0187] wherein RV is the retention volume in milliliters, peak width is in milliliters, peak maximum is the maximum height of the peak, and 1 / 2 height is 1 / 2 the height of the peak maximum; and
[0188] Where RV is the retention volume in milliliters, and peak width is in milliliters, peak maximum is the maximum peak position, tenth height is 1 / 10 the height of the peak maximum, and where post-peak refers to the tail of the peak at a later retention volume than the peak maximum, and where pre-peak refers to the front of the peak at an earlier retention volume than the peak maximum. The plate count of the chromatographic system should be greater than 18,000, and the symmetry should be between 0.98 and 1.22.
[0189] The samples were prepared semi-automatically using the PolymerChar "Instrument Control" software, where the target weight of the sample was set to "2 mg / ml" and the solvent (containing 200 ppm BHT) was added to a septum-capped vial previously sparged with nitrogen via the PolymerChar high temperature autosampler. The samples were dissolved at 160°C for two hours under "low speed" shaking.
[0190] Based on the GPC results, the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR spectrometer was used according to Equations 4 to 6, PolymerChar GPCOne TM The software calculates Mn(GPC), Mw(GPC) and Mz(GPC) from the baseline-subtracted IR chromatogram at each equally spaced data collection point (i) and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) according to Equation 1. Equations 4-6 are as follows:
[0191] and
[0192]
[0193] To monitor the deviation over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by a PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (flow rate (nominal)) of each sample by comparing the RV of the corresponding decane peak in the sample (RV (FM sample)) with the RV of the alkane peak in the narrow standard calibration (RV (calibrated by FM)). It was then assumed that any change in the decane marker peak time was related to a linear change in the flow rate (flow rate (effective)) throughout the run. In order to facilitate the highest accuracy of the RV measurement of the flow marker peak, a least squares fitting procedure was used to fit the peak of the flow marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation was then used to solve for the true peak position. After calibrating the system based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) was calculated using Equation 7: Flow rate (effective) = flow rate (nominal) * (RV (FM calibration) / RV (FM sample)) (Equation 7). Processing of mobile marker peaks by PolymerCharGPCOne TM Software Complete. Acceptable flow rate correction is such that the effective flow rate should be within + / - 0.7% of the nominal flow rate.
[0194] experiment
[0195] The polymers and polymer blends are listed below in Table 1A.
[0196] Table 1A: Polymers and Polymer Blends
[0197]
[0198]
[0199] *See Synthesis below.
[0200] NA = not applicable.
[0201] For each blend in Table 1A, density and melt flow rate (MFR) or melt index (MI) were calculated from the following corresponding equations. The density equation for the blend is as follows, where w a and w b are the corresponding weight fractions of the blend components, and p a and p b are the corresponding densities of the blend components: The MFR equation of the blend is as follows, where w a and w b are the weight fractions of the blend components, and MFR a and MFR b is the corresponding MFR value of the blend components: The MI equation of the blend is as follows, where w a and w b are the corresponding weight fractions of the blend components, and MI a and MI b is the corresponding MI value of the blend components: Each blend in Table 1A was prepared by mixing the corresponding polymer components (pellets) together under vigorous shaking to form a pellet blend.
[0202] Pilot-scale synthesis of OBC 1, 2, 3, 4 and 5
[0203] All raw materials (ethylene and 1-octene) and process solvents (narrow boiling range high purity isoparaffin solvent, Isopar-E) were purified with molecular sieves before introduction into the reaction environment. Hydrogen was supplied under pressure in high purity grades without further purification. The reactor monomer feed stream was pressurized to greater than the reaction pressure via a mechanical compressor. The solvent and comonomer feed were pressurized to greater than the reaction pressure via a pump. Each catalyst component was manually diluted in batches with the purified solvent and pressurized to greater than the reaction pressure. All reaction feed streams were measured with mass flow meters and independently controlled with a computer automated valve control system.
[0204] The continuous solution polymerization reactor consists of the following: a continuous stirred tank reactor (CSTR); or a non-adiabatic isothermal circulating loop reactor filled with liquid, which simulates a continuous stirred tank reactor with heat removal. All fresh solvents, monomers, comonomers, hydrogen and catalyst component feeds can be controlled independently. By passing the feed stream through a heat exchanger, the total fresh feed stream (solvent, monomer, comonomer and hydrogen) to the reactor is temperature-controlled to maintain a single solution phase. The catalyst component is injected into the polymerization reactor through a specially designed injection plug. The computer controls the main catalyst component (catalyst 1 of Table 1B) to feed to maintain the reactor monomer conversion under the specified target. The molar ratio of the second polymerization catalyst feed (catalyst 2 of Table 1B) to the total catalyst feed is adjusted to maintain the desired separation between the polymer soft segment and the hard segment. The cocatalyst 3 component is fed based on the calculated specified molar ratio with the catalyst component. The cocatalyst 4 component is fed to maintain a constant specified concentration in the reactor. Immediately following each reactor feed injection location, the feed stream is mixed with the circulating polymerization reactor contents using static mixing elements. For a loop reactor configuration, the contents of the reactor are continuously circulated through a heat exchanger that is responsible for removing much of the heat of reaction and where the temperature on the coolant side is responsible for maintaining an isothermal reaction environment at a specified temperature. Circulation of the reactor contents is provided via a pump for a loop reactor or via an agitator for a CSTR.
[0205] The reactor effluent enters a zone where it is deactivated by adding and reacting with a suitable reagent (water). At this same reactor outlet location, other additives are added for polymer stabilization. After the catalyst is deactivated and the additives are added, the reactor effluent enters a devolatilization system in which the polymer is removed from the non-polymer stream. The separated polymer melt is granulated and collected. The non-polymer stream is: 1. transferred to waste, or 2. various devices that separate most of the ethylene removed from the system. In the second case, most of the solvent and unreacted comonomer are recycled back to the reactor after passing through the purification system. A small amount of solvent and comonomer are removed from the process. The polymerization conditions of the polymer are further provided in Table 1C.
[0206] Table 1B: Catalysts and co-catalysts
[0207]
[0208] Table 1C: Polymerization conditions
[0209]
[0210]
[0211] Composition: Inventive Examples 1-10 and Comparative Examples A and B
[0212] Compounding
[0213] Inventive Compositions Inventive Examples 1-10 and Comparative Examples A and B are shown in Tables 5 to 8B below. For each composition (TPO), the components (pellets and / or pellet blends) were mixed in a twin screw extruder; it was a COPERION ZSK-26 mm twin screw extruder equipped with a water bath and a strand cutter. The extruder configuration and temperature profile for each composition are shown in Table 2. All components except talc were dry mixed in a plastic bag and then fed to the main feed throat via a loss-in-weight feeder. Talc was fed to the main feed throat via a separate powder feeder.
[0214] Table 2: Compounding conditions
[0215] ZSK-26 Region 1 Area 2 Area 3 Region 4 Area 5 Area 6 Area 7 Area 8 Extruder Set point 130℃ 180℃ 200℃ 200℃ 200℃ 200℃ 200℃ 200℃ 300RPM
[0216] Injection Molded Type I and ISO Tensile Test Bars
[0217] ASTM D638 Type I tensile bars and ISO tensile bars were injection molded on a TOYO injection molding machine. Through various control experiments, the molding conditions were optimized to ensure that the defects in the tensile bar parts were minimal. The key injection molding settings are listed in Tables 3A and B. The tensile bar was used for all mechanical properties except dart ductility. See Tables 5 to 8B below.
[0218] Table 3A: Injection molding conditions for ASTM D638 Type I tensile test bars
[0219]
[0220] Table 3A: Injection Molding Conditions for ISO Tensile Test Bars
[0221]
[0222] Injection molding—TPO disc
[0223] TPO discs (4 inch diameter) with a thickness of 1 / 8 inch (3.2 mm) were injection molded on a TOYO injection molding machine. Through various control experiments, the molding conditions were optimized to ensure minimal defects in the tensile test bar parts. The key injection molding settings are listed in Table 4. The discs were used for optical properties and dart drop ductility. See Tables 5 to 8B below.
[0224] Table 4: Injection settings
[0225]
[0226] Research
[0227] A. Effect of Tg on TPO Performance-Mechanical Properties
[0228] A summary of the TPO properties of the two compositions (inventive vs. comparative) is shown in Table 5 below (Tg POE D <(Tg POE B -10°C). Compared to the comparative composition (Comparative Example A), the inventive composition (Inventive Example 1) has improved low temperature impact properties (see Izod notched value and dart drop ductility) at comparable optical properties (see transmittance at room temperature).
[0229] Table 5: Mechanical and optical properties
[0230]
[0231]
[0232] Note that room temperature = 23°C.
[0233] *See Drop Dart Ductility Test Method.
[0234] a) Note that since "100% ductility" is achieved at -40°C, "100% ductility" can also be achieved at higher temperatures, such as -30°C, -20°C, -10°C, and 0°C.
[0235] B. Effect of Crystallinity on TPO Performance-Optical Properties
[0236] The effect of crystallinity on TPO properties of the inventive and comparative compositions is shown below in Table 6. Comparative Example B and Inventive Example 2 have comparable physical properties, but the change in optical transmittance from room temperature to 60°C is significantly reduced for Inventive Example 2.
[0237] Table 6: Mechanical and optical properties
[0238]
[0239] Note that room temperature = 23°C.
[0240] *Method described in DSC test method.
[0241] a) Note that since "100% ductility" is achieved at -40°C, "100% ductility" can also be achieved at higher temperatures, such as -30°C, -20°C, -10°C, and 0°C.
[0242] C. Optical diffusion
[0243] Optical diffusivity or light diffusivity is a measure of the ability of a material to transmit light from a light source through the material in a uniform manner without characterizing one or more features of the pattern of the light source (eg, LED lighting) beneath the material. Figure 3Depicted are photographs of two TPO boards on top of an LED light source, each board having a thickness of 3.2 mm. The board on the left was prepared using a comparative composition (hPP A / POE A=65 / 35wt / wt). The board on the right was prepared using an inventive composition (hPP A / POE D=65 / 35wt / wt). Comparative compositions typically used for transparent tough applications show a transmittance of greater than 60%, however, the composition has an uneven transmittance (or poor diffusion) because a large number of hot spots caused by the light intensity from the LED device can be seen through the board. In addition, the parts formed from the comparative composition have poor impact properties (0% dart ductility at -40°C). The inventive (translucent TPO) composition provides a greater amount of uniform transmittance (or good diffusion) at the same thickness (i.e., 3.2 mm), with a significantly lower number of hot spots observed on the board.
[0244] D. Properties of No-Filler and Low-Filler Compositions
[0245] The TPO properties of three unfilled compositions and one low filler composition are shown below in Table 7. Each composition had very good low temperature dart drop ductility, good / consistent light transmittance at the operating temperature, and good light diffusion.
[0246] Table 7: Mechanical and optical properties
[0247]
[0248] Note that room temperature = 23°C. a) Note that since "100% ductility" was achieved at -40°C for each composition, "100% ductility" can also be achieved at higher temperatures, such as -30°C, -20°C, -10°C, and 0°C.
[0249] Variants of E.hPP
[0250] Table 8B summarizes the stiffness (flexural modulus) / toughness (Izod notch and dart ductility) / flowability (MFR) of several compositions, each containing a different type of polypropylene homopolymer, as shown in Table 8A. Inventive Examples 9 and 10 show significantly improved stiffness / toughness / flowability. Table 8A depicts the DSC peaks identified from the first cooling curve of each of Inventive Examples 9 and 8'. As shown in the table, the better performing composition (Inventive Example 9) has two separate crystallization peaks, each at a temperature above 100°C, and the highest temperature crystallization peak occurs at a temperature above 120°C.
[0251] Table 8A: Composition and properties
[0252]
[0253] Table 8B: Composition and properties continued
[0254]
[0255] Note that room temperature = 23°C.
[0256] a), b) Note that since for each composition, "100% ductility" is achieved at -40°C, "100% ductility" can also be achieved at higher temperatures, such as -30°C, -20°C, -10°C and 0°C.
[0257] F. Add optical brightener and polypropylene clarifier
[0258] Inventive Example A was formulated to incorporate an optical brightener and polypropylene clarifier masterbatch to reduce the yellowness of molded parts, which may be due to the addition of talc filler. The formulation and TPO properties are shown in Table 9A and Table 9B. After making parts, it was observed that the Inventive Example A formulation containing optical brightener and clarifier had a visually less yellowness than the formulation without optical brightener and clarifier (i.e., Inventive Example 6), while still providing comparable levels of light transmittance and ductility at -40°C.
[0259] Table 9A. Composition of compounds containing optical brighteners and clarifying agents
[0260] Preparation ingredients (by portion) Invention Example A hPP 1 16.8 hPP2 35.8 POE D 24.8 POE 1 10 AO1 0.6 Filler A 5 CF 4 total 100
[0261] Table 9B. Properties of Compounds Containing Optical Brighteners and Clarifiers
[0262] characteristic Invention Example A Flexural modulus (MPa) 1760 <![CDATA[At 23 °C, the Charpy V-notch (kJ / m 2 )]]> 38.5 <![CDATA[At -30 °C Charpy V-notch (kJ / m 2 )]]> 4.2 Light transmittance at room temperature (3.2 mm thick component) 37.6 Dart drop ductility%, 3.3m / s (-40℃) 100
[0263] Note that since "100% ductility" was achieved at -40°C for each composition, "100% ductility" can also be achieved at higher temperatures, such as -30°C, -20°C, -10°C, and 0°C.
[0264] Composition: Inventive Examples BD and Comparative Example C
[0265] Compounding
[0266] Inventive compositions BD and Comparative Example C are shown in Table 9 below. For each composition (TPO), the components (see Table 10) were compounded in a twin screw extruder (TSE) (Model: Coperion ZSK 18MEGAlab), which was a high speed (max: 1200 RPM), high torque (max specific torque: 18 Nm / cm3) 18 mm co-rotating TSE, L / D=40 and Do / Di=1.55. The processing conditions and screw designs for the compounded materials are provided in Table 11, respectively.
[0267] Table 10: Composition
[0268]
[0269] Table 11: Processing conditions used in the twin screw extruder for compounding
[0270] ZSK-18 Region 1 Area 2 Remaining area Extruder Feed rate Set point 140℃ 180℃ 190℃ 300RPM 10lbs / hr
[0271] Injection Molded I-Type Tensile Test Bar
[0272] Equipped with Master Unit Die manufactured by Master Precision 100 ton injection molding machine (model: Sodick TM ASTM D638 Type I tensile test bars (0.125 inch thick) were injection molded on a GL100A) to produce ASTM D638 Type I tensile test bars (0.125 inch thick) using an insert gate (2.1×19 mm) according to Table I of ASTM D3641-02 and a Z-shaped runner (2 tensile test bars per injection). Through various control experiments, the molding conditions were optimized to ensure minimal defects in the tensile test bar parts. The key injection molding settings are listed in Table 12.
[0273] Table 12: Processing conditions used in injection molding machines
[0274] Zone Z0 temperature (℃) 190 Remaining area temperature (℃) 190 Injection speed (cc / s) 35 Hold time(s) 10 Mold temperature 140 Cooling time(s) 30
[0275] A TPO disk (4 inch diameter) with a thickness of 1 / 8 inch (3.2 mm) was injection molded using an edge gate insert. Through various control experiments, the molding conditions were optimized to ensure minimal defects in the tensile bar part. The disk was used for optical and mechanical characterization. See Table 13 below.
[0276] Table 13: Optical and mechanical properties of Inventive Examples BD and Comparative Example C
[0277]
[0278] Inventive Examples BD were formulated with additional OBC-based modifiers POE 2 to POE 4, which were synthesized under conditions that provided higher densities (0.885 g / cc to 0.902 g / cc). These formulations showed fairly consistent transmittance at both room temperature (23°C) and elevated temperature (60°C), with transmittance differences less than or equal to 6%. It was found that the use of OBC-based modifiers with higher SS T m (SS T m =36°C) has an increased variation between the transmittance at room temperature and the transmittance at 60°C. This is true even when compared to Inventive Example E prepared with POE 4 having a comparative density of about 0.902 g / cc.
Claims
1. A composition comprising a first composition, wherein the first composition comprises at least the following components a and b: a) at least one ethylene / α-olefin multi-block interpolymer comprising a density of ≥ 0.870 g / cc and a soft segment melting temperature (SS-Tm) of ≤ 35°C; b) a polymer composition comprising at least one propylene homopolymer, and The component a is present in an amount of ≤50% by weight based on the weight of components a and b.
2. The composition of claim 1, wherein the ethylene / α-olefin multi-block interpolymer (of component a) has a density from 0.870 g / cc to 0.910 g / cc.
3. The composition of claim 1 or claim 2, wherein the ethylene / α-olefin multi-block interpolymer (of component a) has a SS-Tm of -20°C to 35°C.
4. The composition of any one of claims 1 to 3, wherein the ethylene / α-olefin multi-block interpolymer (of component a) is an ethylene / α-olefin multi-block copolymer.
5. The composition of any one of claims 1 to 4, wherein the ethylene / α-olefin multi-block interpolymer (of component a) has a melt index (I2) of 0.1 g / 10 min to 50 g / 10 min.
6. The composition according to any one of claims 1 to 5, wherein the propylene homopolymer (of component b) has a melt flow rate (MFR) of 1.0 to 200 g / 10 min.
7. The composition according to any one of claims 1 to 6, wherein component b comprises at least two propylene homopolymers (first and second), and wherein the melt flow rate (MFR hPP1 ) is greater than the melt flow rate (MFR) of the second homopolymer hPP2 ).
8. The composition according to claim 7, wherein the MFR hPP1 / MFR hPP2 The ratio is "greater than 1" to 50.
9. The composition of claim 7 or claim 8, wherein the weight ratio of the first propylene homopolymer to the second propylene homopolymer is from 0.1 to 10.
10. The composition according to any one of claims 1 to 9, wherein the weight ratio of component b to component a is from 1.0 to 10.
0.
11. The composition of any one of claims 1 to 10, wherein the first composition comprises 80 to 100 wt% of components a and b in total, based on the weight of the first composition.
12. The composition according to any one of claims 1 to 11, wherein the first composition comprises at least two crystallization peaks (a first peak and a second peak), and wherein the second peak and the first peak are peaks having the highest and second highest crystallization temperatures, respectively, and wherein the second peak and the first peak each independently have a crystallization temperature of ≥100°C. 13 . The composition according to claim 12 , wherein the first crystallization peak has a crystallization temperature of 100° C. to 140° C.
14. The composition of claim 12 or claim 13, wherein the second crystallization peak has a crystallization temperature that is ≥5°C higher than the crystallization temperature of the first crystallization peak.
15. The composition according to any one of claims 1 to 14, wherein the composition has an MFR of ≥ 5.0 g / 10 min.
16. The composition according to any one of claims 1 to 15, wherein the light transmittance (3.2 mm thickness) of the composition at room temperature (23°C) is ≥ 30%.
17. The composition according to any one of claims 1 to 16, wherein the composition has a transmittance change % satisfying the following relationship: [(transmittance at room temperature (23°C) (3.2 mm thickness)) - (transmittance at 60°C (3.2 mm thickness))] ≤ 15%.
18. The composition according to any one of claims 1 to 17, wherein the composition has the following properties a) to g): a) MFR ≥ 10 g / min, b) light transmittance at room temperature (3.2 mm thickness) ≥30%, c) dart drop ductility at -10℃ (2.2m / s) ≥90%, d) cantilever beam notch at -30℃ ≥4kJ / m 2 , e) cantilever beam notch at 23℃≥35kJ / m 2 , f) flexural modulus ≥ 800 MPa, and g) [(light transmittance (3.2 mm thickness) at room temperature (23°C)) - (light transmittance (3.2 mm thickness) at 60°C))] ≤ 10%.
19. An automotive article comprising at least one component formed from the composition of any one of claims 1-18.
20. An article comprising at least one component formed from the composition of any one of claims 1-18.
Citation Information
Patent Citations
Illuminated panel assembly
GB2552996A
Painted polyolefin articles
US10557005B2
Vehicular component incorporating concealable indicia with controlled light transmission
US20120313392A1
Illuminated translucent body panels and methods therefor
US20150291085A1
Impact modification of filled thermoplastics
US5925703A